A covalent organic framework-based olefin polymerization catalyst and its preparation method and application

Zr metal catalyst Zr-TdDa with pore methylated COF supports solves the problem of the lack of covalent organic frame-based olefin polymerization catalyst in the prior art, and realizes covalent organic frame materials with high porosity and high catalytic activity, which is suitable for Heterophase catalytic olefin polymerization, especially in ethylene polymerization, exhibits excellent catalytic properties.

CN116731225BActive Publication Date: 2024-12-17ANQING NORMAL UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310451792.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-24
Publication Date
2024-12-17
Estimated Expiration
2043-04-24

AI Technical Summary

Technical Problem

The prior art has failed to effectively provide a covalent organic framework-based olefin polymerization catalyst, especially in the related properties of ethylene polymerization and low pressure catalytic ethylene polymerization.

Method used

Zr metal catalyst Zr-TdDa with pore methylated COF as support was used by using 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tris(2,6 -dimethylaniline) reacted with 2,5-dihydroxyterephthaldehyde to prepare the active sample TdDa, and reacted with ZrCl4, and prepared by the cryo-sealing method to form a functional material with high porosity and high catalytic activity.

Benefits of technology

A covalent organic framework-based olefin polymerization catalyst with high catalytic activity and thermal stability has high yields and is suitable for the field of heterogeneous catalytic olefin polymerization, especially in ethylene polymerization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116731225B_ABST
    Figure CN116731225B_ABST
Patent Text Reader

Abstract

The invention discloses a covalent organic framework-based olefin polymerization catalyst and a preparation method and application thereof, belonging to the technical field of spatial confined catalysis and COF materials. The preparation method comprises the following steps: (1) preparing an active sample TdDa: mixing 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tris(2,6-dimethylaniline), 2,5-dihydroxyterephthalaldehyde, o-dichlorobenzene and ethanol to obtain an active sample TdDa; (2) preparing a catalyst Zr-TdDa: placing TdDa and ZrCl4 in a reaction vessel, injecting tetrahydrofuran under vacuum, heating and stirring, centrifuging, and drying to obtain dry Zr-TdDa. Beneficial effects: The catalyst of the invention is a two-dimensional metallized COF with a novel topological structure. The synthesis method is simple, the pores are methylated, the raw materials are easily available, and the crystalline material exhibits high porosity and catalytic activity. The results of ethylene polymerization test show that it can be used as an olefin polymerization in the field of heterogeneous catalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of spatial confinement catalysis and COF materials, and specifically relates to a covalent organic framework-based olefin polymerization catalyst and a preparation method and application thereof. Background Art

[0002] Covalent organic frameworks (COFs) have great potential for controlling the composition, surface area, particle size, particle size distribution, and porosity of (co)polymers due to their structural diversity, channel modifiability, and uniformly distributed metal sites in the framework, which allow for effective regulation of the microenvironment around the catalytic sites, thereby enabling controlled polymerization outcomes and tailored polymer properties during heterogeneous polymerization processes.

[0003] Metallated COFs (MCOFs) are a class of highly stable porous materials with diverse structures and compositions. The spatial confinement of the matrix in the pores can induce specific host-guest interactions with the MCOFs framework, thereby promoting the efficient catalytic reaction. MCOFs have the following advantages: (i) The pore size of MCOFs can be fine-tuned by the choice of monomers, thus forming a size-selective catalytic closed confinement environment. (ii) The metal ions are fixed on the pore walls, which can prevent them from aggregating and losing catalytic performance. (iii) The structure of MCOFs is highly stable to harsh chemical systems, including boiling water, strong acids and strong bases.

[0004] The Chinese patent application document with publication number CN107433205A discloses a covalent organic framework-supported cobalt catalyst and its preparation and application, and specifically discloses that the covalent organic framework (COFs) material supports metal cobalt for catalyzing carbon dioxide and epoxy compounds to synthesize cyclic carbonate compounds. The structural unit of the material contains a cobalt-porphyrin complex, which can be used to catalyze the reaction between carbon dioxide and epoxy compounds. In addition, COFs has a large specific surface area and an open pore structure, which can enhance the adsorption capacity of carbon dioxide. Therefore, the material can simultaneously achieve adsorption and catalytic conversion of carbon dioxide gas to generate cyclic carbonates under normal temperature and pressure conditions. The reaction substrate types can be expanded, the reaction yield is high, the catalyst can be recycled, the operation is simple, and the product added value is high. However, the patent does not involve properties related to ethylene polymerization and low-pressure catalytic ethylene polymerization. Summary of the invention

[0005] The technical problem to be solved by the present invention is how to provide a covalent organic framework (COFs)-based olefin polymerization catalyst.

[0006] The present invention solves the above technical problems through the following technical means:

[0007] The Zr metal catalyst of the present invention, which is Zr-TdDa, with a channel methylated COF as a carrier, wherein Da is 2,5-dihydroxyterephthalaldehyde, has a structural formula of Td is 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tris(2,6-dimethylaniline), and its structural formula is The metal source is ZrCl4. Da and Td are synthesized, and other reagents are commercially available.

[0008] The first aspect of the present invention provides a method for preparing a covalent organic framework-based olefin polymerization catalyst, comprising the following steps:

[0009] (1) Preparation of active sample TdDa:

[0010] a. 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tris(2,6-dimethylaniline) (Td), 2,5-dihydroxyterephthalaldehyde (Da), o-dichlorobenzene and ethanol were mixed, ultrasonically treated, and then an acetic acid aqueous solution was added. The mixture was then degassed by freeze-pump-thaw cycles, the reaction mixture was sealed, cooled to room temperature, vacuum filtered, and washed to obtain a wet sample.

[0011] b. The wet sample is transferred to an extractor, washed with an organic solvent, and then washed with liquid carbon dioxide, and then heated to make the carbon dioxide reach a supercritical state, and vented to ambient pressure; and then vacuumed under heating to obtain an active sample TdDa;

[0012] (2) Preparation of catalyst Zr-TdDa:

[0013] The active sample TdDa and ZrCl4 obtained in step (1) are placed in a reaction container, tetrahydrofuran (THF) is injected under vacuum, heated and stirred, centrifuged, and dried to obtain dry Zr-TdDa.

[0014] Beneficial effects: The present invention first reacts 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tris(2,6-dimethylaniline) and 2,5-dihydroxyterephthalaldehyde to prepare an active sample TdDa, and then reacts with ZrCl4 to obtain a Zr metal catalyst Zr-TdDa with a pore methylated COF as a carrier. The catalyst is prepared by a freezing-sealing tube method, has a high yield, high thermal stability, and exhibits high catalytic activity, and is expected to be applied in the field of heterogeneous catalytic olefin polymerization.

[0015] Preferably, the molar ratio of Td to Da in step a is 1-3:2-4.

[0016] Preferably, the molar ratio of Td to Da in step a is 2:3.

[0017] Preferably, the ultrasonic treatment time in step a is 8-15 min.

[0018] Preferably, the reaction temperature in step a is 100-140° C., and the reaction time is 2-5 days.

[0019] Preferably, the organic solvent in step b is dioxane and tetrahydrofuran.

[0020] Preferably, the vacuuming under heating in step b is specifically: vacuuming at a speed of 0.1-0.2 MPa / min at 100-140° C. for 10-14 hours.

[0021] Preferably, in step (2), the mass ratio of TdDa to ZrCl4 is 3-5:0.5-1.5.

[0022] Preferably, in step (2), the mass ratio of TdDa to ZrCl4 is 4:1.

[0023] Preferably, the heating temperature in step (2) is 60-80°C.

[0024] Preferably, the stirring time in step (2) is 10-14 hours.

[0025] Preferably, the drying in step (2) is vacuum drying at 30-50° C. for 10-14 h.

[0026] The second aspect of the present invention provides a covalent organic framework-based olefin polymerization catalyst prepared by the above method.

[0027] The third aspect of the present invention provides an application of the covalent organic framework-based olefin polymerization catalyst prepared by the above method in olefin polymerization.

[0028] The advantages of the present invention are:

[0029] 1. The present invention first reacts 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tris(2,6-dimethylaniline) and 2,5-dihydroxyterephthalaldehyde to prepare an active sample TdDa, and then reacts with ZrCl4 to prepare a Zr metal catalyst Zr-TdDa with a pore methylated COF as a carrier. The catalyst is prepared by a freezing-sealing tube method, has a high yield, high thermal stability, and exhibits high catalytic activity, and is expected to be applied in the field of heterogeneous catalytic olefin polymerization.

[0030] 2. The Zr metal catalyst with channel methylated COF as carrier is the first functional material with high porosity and high catalytic activity constructed by using channel functionalized COFs.

[0031] 3. The pore-functionalized two-dimensional metallized COF (Zr-TdDa) of the present invention can be further developed and applied as an ethylene polymerization catalyst with large pore confinement.

[0032] 4. The catalyst of the present invention is a two-dimensional metallized COF with a novel topological structure. Its synthesis method is simple, the pores are methylated, the raw materials are easily available, and its crystalline material exhibits high porosity and catalytic activity. The results of ethylene polymerization test studies show that it can be used as an olefin polymerization in the field of heterogeneous catalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a (100) crystal plane image of the covalent organic framework-based olefin polymerization catalyst prepared in Example 1 of the present invention;

[0034] Figure 2 is a powder diffraction pattern of the covalent organic framework-based olefin polymerization catalyst prepared in Example 1 of the present invention;

[0035] Figure 3 1 are infrared spectra of the covalent organic framework-based olefin polymerization catalyst prepared in Example 1 of the present invention, wherein (a) is the FTIR spectrum of TdDa, and (b) is the FTIR spectrum of Zr-TdDa;

[0036] Figure 4 1 is an X-ray photoelectron spectrum of the covalent organic framework-based olefin polymerization catalyst prepared in Example 1 of the present invention, wherein (a) is an X-ray photoelectron spectrum of TdDa, (b) is a Zr 3d XPS spectrum of Zr-TdDa, (c) is a comparison of the N1s peaks on the imine bonds in TdDa and Zr-TdDa, and (d) is a comparison of the O1s peaks of the phenolic hydroxyl groups in TdDa and Zr-TdDa;

[0037] Figure 5 are scanning electron microscope images of the covalent organic framework-based olefin polymerization catalyst prepared in Example 1 of the present invention, wherein (a) is a scanning electron microscope image of TdDa, and (b) is a scanning electron microscope image of Zr-TdDa;

[0038] Figure 6 1 is a graph of N2 adsorption / desorption of the covalent organic framework-based olefin polymerization catalyst prepared in Example 1 of the present invention, wherein (a) is a porosity comparison graph of TdDa and Zr-TdDa, and (b) is a pore size distribution graph of TdDa. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] The invention discloses a Zr metal catalyst with a channel methylated COF as a carrier, namely Zr-TdDa, wherein Da is 2,5-dihydroxyterephthalaldehyde and Td is 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tris(2,6-dimethylaniline).

[0041] Embodiment 1:

[0042] A method for preparing a covalent organic framework-based olefin polymerization catalyst comprises the following steps:

[0043] (1) Preparation of active sample TdDa:

[0044] a. Td (14 mg, 0.04 mmol), Da (10 mg, 0.06 mmol), dichlorobenzene (1 mL) and ethanol (1 mL) were placed in a 15 mL Schlenk tube (OD 26 × L 70 mm) and mixed. After ultrasonic treatment for 10 minutes, 3 M acetic acid aqueous solution (200 uL) was slowly added, and then degassed by freeze-pump-thaw cycle. The tube was sealed and reacted at 120 ° C for 3 days; after cooling to room temperature, the yellow product was collected by vacuum filtration and washed with acetone 3 times to obtain a wet sample;

[0045] b. The wet sample was then transferred to a Soxhlet extractor, first washed with dioxane for 24 hours, then washed with tetrahydrofuran for 24 hours to thoroughly clean the sample, and then washed with liquid carbon dioxide 5 times, and then the system was heated to 45°C to make the carbon dioxide reach a supercritical state and slowly vented to ambient pressure; the product was then vacuumed at 120°C at a speed of 0.15 MPa / min for 12 hours to obtain an active sample TdDa;

[0046] (2) Preparation of catalyst Zr-TdDa:

[0047] Weigh 20.0 mg TdDa and 5.0 mg ZrCl4 respectively into a 50 mL two-necked flask, inject 2.0 mL THF under vacuum, and slowly stir at 66°C for 12 h; centrifuge the obtained black solid from the suspension, wash with THF 4-5 times, and vacuum dry at 40°C for 12 h to obtain dry Zr-TdDa.

[0048] The catalyst Zr-TdDa prepared in this example: In the XRD spectrum, the strong peak at 3.04° corresponds to the (100) plane of TdDa (such as Figure 1 ), while the weak peaks at 5.26°, 5.88°, and 7.80° correspond to its (110), (200), and (210) crystal planes. It is noteworthy that no additional peaks are observed in the XRD pattern of Zr-TdDa, indicating that the crystal structure is maintained after the addition of Zr (as shown in Figure 2 The instrument used was an X-ray powder diffractometer (model D8Advance, Bruker).

[0049] The characteristic infrared absorption peak of the catalyst Zr-TdDa is (KBr, cm -1 ): In the FTIR spectrum of TdDa, -NH2 of Td (3312~3406cm -1 ) and Da-CHO (1704cm -1 ) disappeared, while at 1623cm -1 The emergence of a new imine bond (-C=N-) characteristic peak indicated the successful preparation of TdDa (e.g. Figure 3 It is worth noting that the FTIR spectrum of Zr-TdDa shows a peak at 464 cm -1 The stretching vibration bands indicate the formation of Zr-O bonds, i.e., Zr 4+ Coordinate with the O atom on the phenolic hydroxyl group (such as Figure 3 (b)). The instrument used is a FT-IR instrument (model VECTOR-22, Bruker).

[0050] Photoelectron spectroscopy analysis of the above catalyst Zr-TdDa: The X-ray photoelectron spectrum (XPS) of TdDa consists of three groups of element peaks: C, N and O, while new Zr and Cl peaks were detected in Zr-TtDa (such as Figure 4 The Zr 3d XPS spectrum of Zr-TdDa provides the Zr 3d 5 / 2 At 183.01 eV and Zr 3d 3 / 2 At the binding energy peak of 185.31 eV (such as Figure 4 (b)). Compared with TdDa (532.81 eV), the O1s peak of the phenolic hydroxyl group in Zr-TdDa (532.63 eV) slightly shifts downward, which is attributed to the coordination of the O atom on the phenolic hydroxyl group with Zr 4+ The coordination effect (such as Figure 4 (d)). Compared with TdDa (399.05 eV), the N1s peak on the imine bond in Zr-TdDa (399.24 eV) shifts slightly upward, which is attributed to the coordination of the N atom on the imine bond with Zr4+ The coordination effect (such as Figure 4 These results indicate that the N atom on the imine bond and the O atom on the phenolic hydroxyl group tend to react with Zr 4+ Chelate to form a stable six-membered chelate ring, Zr 4+ The other surrounding coordination sites are surrounded by three Cl - and one THF molecule to achieve charge balance. The instrument used was an XPS instrument (model K-alpha, Thermo Fisher Scientific).

[0051] Surface morphology analysis of the above catalyst Zr-TdDa: Scanning electron microscopy (SEM) shows that Zr-TdDa and TdDa are mainly in the form of flakes (e.g. Figure 5 The instrument used was a SEM instrument (model SMART APEXⅡ, Bruker AXS).

[0052] The above catalyst Zr-TdDa was tested for N2 adsorption at 77K: The porosity of TdDa and Zr-TdDa was studied by N2 adsorption / desorption measurements at 77K (e.g. Figure 6 (a) shows that the BET surface area of ​​TdDa is 1090.45 m 2 g -1 , due to Zr 4+ With the introduction of TdDa, the specific surface area is almost larger than that of Zr-TdDa (510.63m 2 g -1 ) has a surface area twice as high. The pore size distribution shows that most of the pores of TdDa are concentrated in (like Figure 6 (b)). The instrument used is a BET instrument (model ASAP 2460 Micromeritics).

[0053] The Zr metal catalyst supported on the channel methylated COF, namely Zr-TdDa, was further characterized as follows:

[0054] Study on the performance of ethylene polymerization of Zr metal catalyst (Zr-TdDa) supported by channel methylated COF:

[0055] The results of Zr-TdDa for low-pressure polymerization of ethylene are shown in Table 1. The catalytic activity and weight-average molecular weight increase with increasing ethylene pressure (as shown in Examples 1 to 3 in Table 1 below). In order to study the effect of the amount of cocatalyst methylaluminoxane (MAO) on the catalytic performance of these Zr-COFs / MAO systems, we conducted ethylene polymerization experiments with different MAO amounts and found that the catalytic activity increased with increasing MAO amounts (as shown in Examples 4 to 6 in Table 1 below). This may be due to more metal sites being activated as catalytic sites and faster alkyl chain removal rates. At Al / Zr = 2000 mol / mol, the catalytic activity reached a maximum value of 4.32×10 4 g PE mol Zr -1 h -1 .

[0056] Table 1 Ethylene polymerization using Zr-TdDa

[0057]

[0058] a Activity = mass of ethylene consumed per mole of exchange metal per hour (g PE ·mol Zr -1 ·h -1 ). b The weight average molecular weight (M) was determined by high temperature gel permeation chromatography. w ), number average molecular weight (M n ) and polydispersity index (D). Melting point (T) was determined by differential scanning calorimetry (DSC). M ). d Al / Zr=1000 mol / mol. e Al / Zr=1500 mol / mol. f Al / Zr=2000mol / mol.

[0059] Embodiment 2:

[0060] A method for preparing a covalent organic framework-based olefin polymerization catalyst comprises the following steps:

[0061] (1) Preparation of active sample TdDa:

[0062] a. Td (0.02 mmol), Da (0.04 mmol), dichlorobenzene (1 mL) and ethanol (1 mL) were placed in a 15 mL Schlenk tube (OD 26 × L 70 mm) and mixed. After ultrasonic treatment for 8 minutes, 3 M acetic acid aqueous solution (200 uL) was slowly added, and then degassed by freeze-pump-thaw cycle. The tube was sealed and reacted at 100 ° C for 5 days; after cooling to room temperature, the yellow product was collected by vacuum filtration and washed with acetone 3 times to obtain a wet sample;

[0063] b. The wet sample was then transferred to a Soxhlet extractor, first washed with dioxane for 24 hours, then washed with tetrahydrofuran for 24 hours to thoroughly clean the sample, and then washed with liquid carbon dioxide 5 times, and then the system was heated to 45°C to make the carbon dioxide reach a supercritical state and slowly vented to ambient pressure; the product was then vacuumed at 100°C at a speed of 0.1 MPa / min for 14 hours to obtain an active sample TdDa;

[0064] (2) Preparation of catalyst Zr-TdDa:

[0065] Weigh 15.0 mg TdDa and 2.5 mg ZrCl4 respectively into a 50 mL two-necked flask, inject 2.0 mL THF under vacuum, and slowly stir at 60°C for 14 h; centrifuge the obtained black solid from the suspension, wash with THF 4-5 times, and vacuum dry at 30°C for 14 h to obtain dry Zr-TdDa.

[0066] Embodiment 3:

[0067] A method for preparing a covalent organic framework-based olefin polymerization catalyst comprises the following steps:

[0068] (1) Preparation of active sample TdDa:

[0069] a. Td (0.06 mmol), Da (0.08 mmol), dichlorobenzene (1 mL) and ethanol (1 mL) were placed in a 15 mL Schlenk tube (OD 26 × L 70 mm) and mixed. After ultrasonic treatment for 15 minutes, 3 M acetic acid aqueous solution (200 uL) was slowly added, and then degassed by freeze-pump-thaw cycle. The tube was sealed and reacted at 140 ° C for 2 days; after cooling to room temperature, the yellow product was collected by vacuum filtration and washed with acetone 3 times to obtain a wet sample;

[0070] b. The wet sample was then transferred to a Soxhlet extractor, first washed with dioxane for 24 hours, then washed with tetrahydrofuran for 24 hours to thoroughly clean the sample, and then washed with liquid carbon dioxide 5 times, and then the system was heated to 45°C to make the carbon dioxide reach a supercritical state and slowly vented to ambient pressure; the product was then vacuumed at 140°C at a speed of 0.2 MPa / min for 10 hours to obtain an active sample TdDa;

[0071] (2) Preparation of catalyst Zr-TdDa:

[0072] Weigh 25.0 mg TdDa and 7.5 mg ZrCl4 respectively into a 50 mL two-necked flask, inject 2.0 mL THF under vacuum, and slowly stir at 80°C for 10 h; centrifuge the obtained black solid from the suspension, wash with THF 4-5 times, and vacuum dry at 50°C for 10 h to obtain dry Zr-TdDa.

[0073] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a covalent organic framework-based olefin polymerization catalyst, characterized in that: The following steps are involved: (1) Preparation of active sample TdDa: a. Mix 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tris(2,6-dimethylaniline), 2,5-dihydroxyterephthalaldehyde, o-dichlorobenzene and ethanol, and after ultrasonic treatment, add acetic acid aqueous solution, and then degas by freeze-pump-thaw cycle, seal the reaction, cool to room temperature, vacuum filter, wash, and obtain a wet sample; the molar ratio of 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tris(2,6-dimethylaniline) to 2,5-dihydroxyterephthalaldehyde is 1-3:2-4; b. The wet sample is transferred to an extractor, washed with an organic solvent, and then washed with liquid carbon dioxide, and then heated to make the carbon dioxide reach a supercritical state, and vented to ambient pressure; and then vacuumed under heating to obtain an active sample TdDa; (2) Preparation of catalyst Zr-TdDa: The active samples TdDa and ZrCl4 obtained in step (1) are placed in a reaction container, tetrahydrofuran is injected under vacuum, heated and stirred, centrifuged, and dried to obtain dry Zr-TdDa; the mass ratio of TdDa to ZrCl4 is 3-5:0.5-1.

5.

2. The method for preparing a covalent organic framework-based olefin polymerization catalyst according to claim 1, characterized in that: In the step a, the molar ratio of 4,4',4"-(1,3,5-triazine-2,4,6-triyl)tris(2,6-dimethylaniline) to 2,5-dihydroxyterephthalaldehyde is 2:

3.

3. The method for preparing a covalent organic framework-based olefin polymerization catalyst according to claim 1 or 2, characterized in that: The ultrasonic treatment time in step a is 8-15 minutes; the reaction temperature in step a is 100-140° C., and the reaction time is 2-5 days.

4. The method for preparing a covalent organic framework-based olefin polymerization catalyst according to claim 3, characterized in that: The organic solvent in step b is dioxane and tetrahydrofuran.

5. The method for preparing a covalent organic framework-based olefin polymerization catalyst according to claim 4, characterized in that: The vacuuming under heating in step b is specifically: vacuuming at a speed of 0.1-0.2 MPa / min for 10-14 hours at 100-140°C.

6. The method for preparing a covalent organic framework-based olefin polymerization catalyst according to claim 1, characterized in that: The mass ratio of TdDa to ZrCl4 in step (2) is 4:

1.

7. The method for preparing a covalent organic framework-based olefin polymerization catalyst according to claim 1, characterized in that: The heating temperature in step (2) is 60-80° C.; the stirring time in step (2) is 10-14 h.

8. The method for preparing a covalent organic framework-based olefin polymerization catalyst according to claim 1, characterized in that: The drying in step (2) is specifically performed by vacuum drying at 30-50° C. for 10-14 hours.

9. A catalyst prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the catalyst prepared by the preparation method according to any one of claims 1 to 8 in olefin polymerization.

Citation Information

Patent Citations

  • Covalent organic frameworks-supported cobalt catalyst and preparation and application thereof

    CN107433205A

  • Zirconium metal coordination polymer and synthesis method thereof and application thereof for catalyzing ethylene polymerization

    CN103965233A

  • Chiral covalent organic framework photocatalyst containing transition metal and preparation method thereof

    CN114805832A

  • Covalent organic framework and catalyst, preparation methods therefor, and applications thereof

    WO2022133843A1